2006
DOI: 10.1096/fj.05-5214fje
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine attenuates the β‐amyloid neurotoxicity through regulating metal homeostasis

Abstract: Nicotine reduces beta-amyloidosis and has a beneficial effect against Alzheimer's disease (AD), but the underlying mechanism is not clear. The abnormal interactions of beta-amyloid (Abeta) with metal ions such as copper and zinc are implicated in the process of Abeta deposition in AD brains. In the present study, we investigated the effect of nicotine on metal homeostasis in the hippocampus and cortex of APP(V717I) (London mutant form of APP) transgenic mice. A significant reduction in the metal contents of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 47 publications
5
46
0
Order By: Relevance
“…Immunoblotting for the APP695 protein showed an 86-kDa product in both neo cells (SH-SY5Y transiently transfected with empty vector) and APPsw cells (SH-SY5Y transiently transfected with APP695sw). Consistent with previous studies [21,22], APPsw cells showed significant increases in expression of APP695 compared with neo cells over time (fig. 1).…”
Section: Resultssupporting
confidence: 92%
“…Immunoblotting for the APP695 protein showed an 86-kDa product in both neo cells (SH-SY5Y transiently transfected with empty vector) and APPsw cells (SH-SY5Y transiently transfected with APP695sw). Consistent with previous studies [21,22], APPsw cells showed significant increases in expression of APP695 compared with neo cells over time (fig. 1).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the nicotinic enhancement of GABA A receptor function could not be prevented by DHβE, though it was supposed that nicotine should produce its modulatory effects via functional α4β2-nAChRs expressed on the neuron. These results echo the findings by Zhang and colleagues that the effect of nicotine against β-amyloid-mediated neurotoxicity could not be blocked by nAChR antagonists [61], suggesting that nicotine may exert its modulatory effects on GABA A receptor-induced currents via a nAChR-independent pathway, or additional mechanisms may exist. For example, SNc DA neurons may express different subtypes of GABA A receptors [62][63][64] and the diversity of GABA A receptors may underlie the complex modulation by nicotine.…”
Section: Discussionsupporting
confidence: 89%
“…Several reports have confirmed that A␤-Cu complexes are increased in AD brain (11,13,40), and plaques can be dissolved by copper chelators (41). Indeed, drugs that target A␤-Cu interaction show therapeutic efficacy in preclinical AD models and early phase clinical trials (16,(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 94%